Program Pengungkapan Sukarela sebagai Alternatif Penyelesaian Pelanggaran Pajak Korporasi atas Kasus Asian Agri Group - Ester Aprilia Diyan Sari; Mohammad Imam Gusthomi (CV. ITTC INDONESIA, 2026)
Corporate tax evasion through transfer pricing manipulation raises questions about whether voluntary-based mechanisms can effectively substitute criminal prosecution in Indonesia. This study examines whether the Voluntary Disclosure Program can function as a legitimate alternative dispute resolution instrument for corporate tax violations, referencing a palm oil conglomerate that manipulated transfer prices through offshore affiliates. Using a normative legal method, the study finds that structural limitations render the program insufficient for resolving complex cross-jurisdictional schemes, prolonging enforcement for over five years without guaranteeing full revenue recovery, while lenient treatment of corporate offenders risks undermining broader tax compliance. These findings suggest the need for a tiered voluntary disclosure framework integrating transfer pricing obligations and cross-border data exchange mechanisms.